Spatial analysis of the infrastructure network in Al-Kahla City - Lazem Bashkh, Researcher. Kazem; Assist .Prof. Dr. Osama Ismail Othman , Assist .Prof. Dr. Osama (Basra studies journal, 2026)
Infrastructure services are one of the most important services that contribute to the growth and development of the city, as their lack or inefficiency leads to an increase in pressure on those services and then their inability to face the increase of the student on them due to the expansion of the size of the city This study came in order to shed light on these services in terms of spatial distribution, adequacy and efficiency, the most important factors affecting them, and knowing the extent of the need The city to it at the present time and the future. The study concluded that through field work and the results of the questionnaire form that liquefied water is not suitable for drinking because of its turbidity and the high percentage of salts and impurities in it, which made the residents of the city rely on desalination plants and household filters as the city of Kahlaa suffers from the lack of a rainwater network and depends on the discharge of the sewage network, which lacks a treatment plant due to the lack of financial allocations where this water is transferred to the trocars Which ends directly in the marshes of the judiciary without any significant treatment, In addition to the deterioration of electrical energy services due to the programmed outage, which made the people rely during the frequent hours of interruption on private generators in the city, as for household waste services, it is suffering from the lack of mechanisms used in the process of transporting this waste, in addition to the lack of a sanitary landfill system site, which lacks most of the Iraqi planning standards.